Desempenho térmico e habitação : uma avaliação comparativa no contexto climático da zona bioclimática 8 - Costa, Sammea Ribeiro Granja Damasceno (2011)
The main objective of this research is to analyze the thermal performance of housing units submitted to a climate environment classified as Bioclimatic Zone 8, established by norm NBR 15220-3 from The Brazilian Association of Technical Standards (ABNT), with the purpose of providing indoor thermal comfort to those housing units occupants. The Brazilian locations selected were the following estate capitals: Belém, PA; Fortaleza, CE; Maceió, AL; Salvador, BA and Rio de Janeiro, RJ. Four different types of graphical modeling for computer simulations were determined, in which: one of them was a reference type, two others were modified according to the standards for the climatic context being analyzed and the fourth type was incremented with a shading device. The study has analyzed the solar radiation exposure in facade areas of four different types of solar orientation and three different time periods, in both summer and winter solstices. In order to evaluate the thermal performance of the building units, Design Builder was the computer simulation software chosen for this study case. Also, a comparative analysis of the final results obtained from the comfort limit based on neutral temperatures, considered acceptable for housing units on hot and humid climate zones, has been carried out. The computer simulations of the thermal performance has confirmed that the increase of the effective areas of the openings for ventilation in accordance with NBR 15220-3 and NBR15575, showed, in most cases, reduction in the indoor air temperature in the simulation models, although none model has shown 100% comfortable hours. Confirming that, though the cities belonging to the same bioclimatic zone, the design strategies are important characteristics to achieve a favorable thermal performance, and consequently, the thermal comfort of its users. Though the cities belonging to the same bioclimatic zone, there are important features for design strategies that are important to achieve a favorable thermal performance, and consequently, the thermal comfort of its users.